VD_FINDINFO Décision / 2022 / 146 vom 8. Februar 2022 - VD Tribunal cantonal (2022)
DÉCISION SUR FRAIS, FRAIS DE LA PROCÉDURE, DÉFENSE DE CHOIX | 426 al. 2 CPP (CH), 429 al. 1 let. a CPP (CH), 430 al. 1 let. a CPP (CH)